PENGEMBANGAN SISTEM INFORMASI APOTEK MENGGUNAKAN JAVA NETBEANS IDE DAN DB MYSQL - Galuh Kumala Dewi Setioko; Muksan SAN Junaidi (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2020)
Recording of drug sales and purchase transactions is a process carried out at the Lillis pharmacy. Currently the transaction process is done manually or still using books that can cause difficulty in knowing the amount of drug stock, the slow recording of transactions, the difficulty of finding expired drug data, the drug return process has difficulty in finding so many transaction notes, bad possibilities that can occur is if the memorandum is lost before the transaction data is entered into the report book, the slowness of making sales and purchasing reports. The purpose of the research is the design, development and application of the drug distribution process using a Java-based NetBeans IDE information system. The design of the information system is modeled into diagrams in UML (Unified Modeling Language) and the method of developing the System Development Life Cycle (SDLC) with the Waterfall model. The test results of the Pharmacy Information System obtained 99% of the interfaces tested properly. The research data was taken from Lillis Pharmacy in 2019. This research is expected to be able to help Lillis Pharmacy to simplify and speed up the processing of drug sales and purchase data optimally.